(untitled) (Academia Science Repository, 2023)
This article discusses non-standard methods of teaching English to cadets of the Air Force Academy language, namely: Student’s Created Activity (task developed by the student) and Contest (competition). The article presents the features of teaching a foreign language in a military university, which contributed to the introduction of an active method of game integrative learning, implemented in game integrative classes. Methods "Student’s Created Activity" and "Contest" allow to solve several problems, namely: to carry out active conscious learning by involving cadets in creative activities and the development of creative thinking. special attention is paid to such a way of working with vocabulary as mental maps (Mind Maps). In addition, the article discusses the conditions necessary to ensure the effectiveness of gaming integrative classes. Examples of integrative activities are also given in the article.